PEMANFAATAN SOSIAL MEDIA INSTAGRAM SEBAGAI SARANA PEMASARAN ALTERNATIF - Gultom, Henry Casandra (JAB (Jurnal Akuntansi & Bisnis), 2017)
The development of the worldâ€™s digital channel has brought people to a new chapter of their behavior in responding to the information. Nowadays, every individual by utilizing the internet media, is able to access anything that becomes their interest, directly. Digital media is growing rapidly, such associal media. Indonesia, as one of the countries with the largest population has the opportunity to maximize this opportunity to boost the development of local entrepreneurship.Digital marketing becomes one of the best solution to answer this challenge. Through theinstagram platform, marketers and brand developers can reach their segmentation efficiently and effectively. By formulating the basic concepts correctly, creating content that fits segmentation and basic concept, maximizing key opinion leaders, brand ambassadors, open endorsers, and premium features, marketers and brand developers will be able to present their products to their target market. The most important output is how to build a positive relationship in the long run and leads customer to the interest in buy back and the build a motive for recommending this product to others.Â Keywords : Marketing, digital marketing, instagram, social media, brand.